Using personality as a predictor of diet induced weight loss and weight management - Munro Irene A; Bore Miles R; Munro Don; Garg Manohar L (BMC, 2011)
Abstract Background A major challenge for successful weight management is tailoring weight loss programs to individual needs. The aim of this study was to investigate whether personality traits could be used to match individuals to a compatible weight loss program that would maximize weight loss. Method Two different weight loss trials were conducted, both with a weight loss greater than 5% the measure of success. Fifty-four individuals, BMI 30-40 kg/m2, either followed a slow, healthy eating weight loss diet (HEWLD) of 5000-6000 kJ/day for 12 weeks (n = 22), or a fast, very low energy diet (VLED) of 3000 kJ/day for 4 weeks (n = 32). Anthropometric measurements were recorded at baseline, at the end of the weight loss period and, for VLED, at the end of 10 weeks of weight maintenance. Personality traits were measured at baseline using the Tangney Self Control Scale plus 3 of the scales from the Five Factor Model - Neuroticism, Conscientiousness and Extraversion. Results The percentage weight loss was significantly greater in VLED (-7.38%) compared to HEWLD (-4.11%), (p < 0.001). Weight loss in HEWLD was positively correlated with Anxiety, a facet of Neuroticism. Weight loss in VLED was positively correlated with Neuroticism (r = 0.5, p < 0.01), and negatively correlated with Dutifulness and Discipline, facets of Conscientiousness, (p < 0.05 for both). No link was observed between weight loss and the personality trait, Self Control, in either HEWLD or VLED. Conclusion The personality factor, Neuroticism, was linked to successful weight loss (that is ≥ 5%) with a particular weight loss treatment, suggesting that there is a potential to use measures of personality to identify appropriate weight loss/management strategies for individuals. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12611000716965